Leadership Practices of State Associations: Does State President Leadership Style Encourage Membership? - Leadership Practices of State Associations: Does State President Leadership Style Encourage Membership? Credentials Display Leslie M. Sizemore (Scholarworks @ WMU, 2022)
Background: This research addressed the "graying" of the professional state occupational therapy association as new clinicians are more frequently making the decision not to join. It is particularly relevant for boards who are attempting to establish and retain members. Method: To assess the leadership styles of presidents of state occupational therapy associations and to examine the impact of leadership style on membership status, this research examined the self-perceived leadership styles of state occupational therapy association presidents, as measured by the Leadership Practices Inventory (LPI), a tool developed by Kouzes and Posner, authors of the Exemplary Leadership Model. It served to answer the following research questions: Is there a statistical difference between the Leadership Practices Inventory (LPI) score of state occupational therapy association presidents and the normed mean score of the LPI? And, is there a correlation between LPI mean scores of state occupational therapy association presidents and the respective state association's membership representation of licensed occupational therapists and student therapists? This quantitative study used survey research design. Results: Sixty percent of state presidents participated. Evidence from this study indicates that state occupational therapy association presidents lead primarily from a transformational leadership style. In addition, those states whose presidents lead from this style demonstrate an overall higher membership status level than those who do not. Conclusion: The results of this study indicate that transformational leadership is related to increased membership status and is relevant to associations as they choose their leaders.